Culturally Responsive Community Based Financial Literacy Education: Practical Implications from a Mixed Methods Study of Financial Educators - Elizabeth J. Tisdell; Edward W. Taylor; Karin Sprow (Adult Education Research Conference, 2011)
This paper provides a summary of findings of a mixed method study of 271 financial literacy educators in community-based programs and offers practical implications for culturally responsive pedagogy.
Keywords: culturally responsive pedagogy; financial literacy; community based education